WEAP Analysis of Water Supply and Demand in Langat Catchment of Malaysia - Khan, M. M. H; Kundai, T.C. (INTI International University, 2022)
Recently, there have been water shortages in the state of Selangor of Peninsular Malaysia due to pollution from surrounding river tributaries, increase in destruction and degradation of water catchments. This study serves to look into the water demand and supply issues by analyzing the trend and relationship between demand and supply of water in Langat catchment, evaluating the current water availability and water demand for different sectors, such as agriculture, industry, and domestic using and analyzing the status of future scenarios of the water supply system. Water Resource Modelling tool called Water Evaluation and Planning (WEAP) obtain meteorological, population and climate data from relevant authorities and entering the data into WEAP which will simulate results based on the data entered and scenarios suggested by the users. The results obtained from the simulation show that an increase in population growth rate will result in increased demand for water, as found that in 2009 the demand for water is 370 million cubic meters and in 2040 it is 560 million in cubic meters, low population growth rate however shows that as population growth rate decreases demand and unmet demand for water decreases which shows that demand for water in 2009 the demand for water is 370 million cubic meters and in it is 280 million cubic meters. Hence this will help water management authorities to plan and allocate available resources accordingly so that it does not affect water availability for future generations.